Molybdenum isotope variations in molybdenite: vapor transport and Rayleigh fractionation of Mo - Hannah, J.; Stein, H.; Wieser, M.; De Laeter, John; Varner, M. (Geological Society of America, 2007)
Molybdenum isotopes in 20 molybdenite samples, dated by the Re-Os method and representing a range of geologic settings, show mass-dependent fractionation spanning 0.63 per atomic mass unit (amu). Previous Mo isotope data for molybdenite reveal variations in fractionation of <0.5/amu. Interpretation of these data is hampered, however, by limited sample numbers in each study, lack of a common standard for interlaboratory comparison, and limited range of geologic settings. Here we show that Mo isotope compositions of molybdenites do not correlate with crystallization temperature, age, geographic distribution, or geologic conditions. Rather, Rayleigh distillation may explain variations of as much as 0.34/amu in a single molybdenite occurrence, exceeding the proposed variability in average continental crust. Vapor transport and rapid precipitation of Mo in propagating fractures may account for isotope fractionation of Mo (and perhaps other metals) at very small scales. If so, the average isotopic composition of Mo at each molybdenite occurrence may be representative of bulk crust. Our results suggest that the isotopic composition of Mo delivered to the oceans is uniform geographically and through geologic time.